2017
DOI: 10.1016/j.memsci.2017.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical removal of hexavalent chromium using electrically conducting carbon nanotube/polymer composite ultrafiltration membranes

Abstract: Hexavalent chromium (Cr(VI)) contamination in drinking water resources remains a challenge in many parts of the United States, as well as in regions affected by industrial pollution. In this study, we demonstrated how electrically conducting carbon nanotube (CNT)polyvinyl alcohol (PVA) composite ultrafiltration (UF) membranes can be used to remove Cr(VI) from water through a combined process of electrostatic repulsion, electrochemical reduction, and precipitation. The impact of different operational (flux, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 55 publications
2
86
0
Order By: Relevance
“…From the cross-sectional SEM image of the PVA-CNT/PS-35 composite membrane (S3 Fig in S1 File), the thickness of the PVA-CNT thin film was determined to be approximately 6 μm compared to the 165 μm thickness of the commercial polysulfone membrane which agrees with previously reported measurements [5,11]. With an approximate 10 μm thickness of the selective layer [5], the length fraction of the support layer, X, was determined to be 0.91.…”
Section: Pva-cnt Membrane Characterizationsupporting
confidence: 87%
See 1 more Smart Citation
“…From the cross-sectional SEM image of the PVA-CNT/PS-35 composite membrane (S3 Fig in S1 File), the thickness of the PVA-CNT thin film was determined to be approximately 6 μm compared to the 165 μm thickness of the commercial polysulfone membrane which agrees with previously reported measurements [5,11]. With an approximate 10 μm thickness of the selective layer [5], the length fraction of the support layer, X, was determined to be 0.91.…”
Section: Pva-cnt Membrane Characterizationsupporting
confidence: 87%
“…Jassby et al [5][6][7][9][10][11] developed methods of coating commercial polymeric UF membranes with a thin layer of a poly(vinyl-alcohol) (PVA) polymer cross-linked with multiwalled carbon nanotubes to form highly electrically conductive PVA-CNT composite membranes. In a study of the effect of moderate applied electric potentials (-1.5 and -3.4 V vs Ag/AgCl references) on fouling of high concentrations (3-5 g/L) of synthetic wastewater containing negatively charged alginic acid during EUF using PVA-CNT composite membranes, Dudchenko and Jassby et al observed substantial fouling inhibition and reduction of operating pressure in a constant flux system [6].…”
Section: Introductionmentioning
confidence: 99%
“…They are either single walled carbon nanotubes (CNTs) or multiwalled carbon nanotubes (CNTs) possessing hexagonal carbon lattice well known for modification of membrane materials due to their low production cost, high purity and easy scaling up characteristics [140]. Wenyan et al [141] reported the fabrication of carbon nanotube (CNT) -Polyvinyl Alcohol (PVA) composite polysulfone Ultrafiltration (UF) membrane for chromium ion removal. Increase in surface charge density of membrane surface results in increased chromium ion removal.…”
Section: Carbon Based Polymeric Nano-composite Membranesmentioning
confidence: 99%
“…Two-way analysis of variance (ANOVA) followed by post hoc Tukey's multiple comparisons tests were performed using Graphpad Prism version 6.01 (Graphpad Software, La Jolla, CA, USA) to assess the statistical differences among the weighted factor means at a significance level of p < 0.05. reported measurements [5,11]. With an approximate 10 µm thickness of the selective layer [5], the length fraction of the support layer, X, was determined to be 0.91.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen, unlike electroultrafiltration processes with electrodes on each side of the membrane, the external electric field terminates with the poly(vinyl-alcohol)carbon nanotube layer, which is upstream of the semipermeable, polymeric membrane. Jassby et al [5][6][7][9][10][11] developed methods of coating commercial polymeric UF membranes with a thin layer of a poly(vinyl-alcohol) (PVA) polymer cross-linked with multiwalled carbon nanotubes to form highly electrically conductive PVA-CNT composite membranes. In a study of the effect of moderate applied electric potentials (-1.5 and -3.4 V vs Ag/AgCl references) on fouling of high concentrations (3-5 g/L) of synthetic wastewater containing negatively charged alginic acid during EUF using PVA-CNT composite membranes, Dudchenko and Jassby et al observed substantial fouling inhibition and reduction of operating pressure in a constant flux system [6].…”
Section: Fig 1 Schematic View Of Crossflow Electroultrafiltration Wimentioning
confidence: 99%